2020
DOI: 10.1155/2020/8811597
|View full text |Cite
|
Sign up to set email alerts
|

Digestive Enzyme Inhibition of Different Phenolic Fractions and Main Phenolic Compounds of Ultra-High-Pressure-Treated Palm Fruits: Interaction and Molecular Docking Analyses

Abstract: The purpose of the present work was to evaluate the inhibitory effects of different phenolic extracts from non- and ultra-high-pressure- (UHP-) treated palm fruits and their main phenolic compounds against pancreatic lipase and α-glucosidase and to further analyze the interaction and inhibitory mechanisms of two main phenolics (caffeic acid and catechin). Results showed that the free, esterified, and insoluble-bound phenolic fractions from the non- and UHP-treated fruits demonstrated good inhibitory effects to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 26 publications
(44 reference statements)
2
9
0
Order By: Relevance
“…However, natural alternatives are sought due to this medication's adverse effect, such as gastrointestinal discomfort, steatorrhea, oily feces, fecal incontinence, and potentially liver damage [209]. Zhou, Zhou, Liu, Zhang, and Cai [33] performed a docking analysis on the inhibitory capacity of caffeic acid and catechin against pancreatic lipase. Their computational analysis using the software SYBYL-X 2.1.1 showed that catechin has more affinity towards the enzyme, as catechin binds to pancreatic lipase with the amino acid residues Ala197, Pro194, Ser195, and Lys198 at the active site by hydrogen bonds.…”
Section: Anti-obesity and Anti-diabeticmentioning
confidence: 99%
See 1 more Smart Citation
“…However, natural alternatives are sought due to this medication's adverse effect, such as gastrointestinal discomfort, steatorrhea, oily feces, fecal incontinence, and potentially liver damage [209]. Zhou, Zhou, Liu, Zhang, and Cai [33] performed a docking analysis on the inhibitory capacity of caffeic acid and catechin against pancreatic lipase. Their computational analysis using the software SYBYL-X 2.1.1 showed that catechin has more affinity towards the enzyme, as catechin binds to pancreatic lipase with the amino acid residues Ala197, Pro194, Ser195, and Lys198 at the active site by hydrogen bonds.…”
Section: Anti-obesity and Anti-diabeticmentioning
confidence: 99%
“…On the other hand, caffeic acid binds to the amino acid residues Ala197, His224, and Lys198 at the active site. However, caffeic acid shows shorter hydrogen bond distances than catechin, which usually represent tight bounds and stronger inhibitory ability [33].…”
Section: Anti-obesity and Anti-diabeticmentioning
confidence: 99%
“…Carbohydrates and fats in food are the main contributors to the body's energy intake, and therefore reducing carbohydrate and/or fat intake is considered an effective way to suppress energy intake [5][6][7]. In the digestive system, carbohydrates and fats need to be digested before they can be absorbed.…”
Section: Introductionmentioning
confidence: 99%
“…Although these clinical drugs are effective, they all have serious side effects. A large number of previous studies have found that many secondary metabolites of edible plants, especially phenolic compounds, have good inhibitory effects toward α-glucosidase and/or pancreatic lipase [6,7,10,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation